Economic Evaluation of the Environmental Impacts of Juice Production: A Case Study of Pomegranate Juice - L. Behrooznia; M. Khojastehpour; H. Hosseinzadeh-Bandbafha (Journal of Agricultural Machinery)
IntroductionPomegranate has gained global popularity due to its high vitamin content and antioxidant properties, attracting fans worldwide. The processing of pomegranate into various products, including pomegranate juice, has become a thriving industry. However, this processing requires significant energy and chemicals—most of which are derived from fossil fuels. The combustion of these fuels releases harmful gases, contributing to global warming, environmental damage, and health risks. The costs tied to these environmental burdens are often overlooked, neglecting the principles of environmental sustainability. Therefore, it is vital to assess the monetary value of the environmental impacts throughout the entire life cycle of pomegranate juice production. This research aims to investigate the costs imposed on society, including the social costs of carbon emissions, damage costs from air pollution, and costs associated with environmental prevention measures related to processing pomegranate juice. Feel free to ask for further changes or adjustments.Materials and MethodsThis study focuses on assessing the environmental impact and associated costs generated during the processing of pomegranate juice in Mashhad, Iran, from 2022 to 2023. The research examines the case study of Saman Bazar Razavi Co. to conduct an environmental impact cost assessment. The study begins by evaluating the environmental impacts associated with the pomegranate juice production process using a life cycle assessment (LCA) approach. The costs related to these impacts are then estimated by multiplying the impact amounts with predetermined monetary coefficients. The study adopts a system boundary that extends from the arrival of the fruit at the factory to the departure of the packaged juice, defining a 160g pack of pomegranate juice as the functional unit (FU). SimaPro software, version 9, is utilized for analyzing the environmental impacts. The evaluation of environmental impact costs encompasses three categories: social costs of carbon emissions, damage costs from air pollution, and costs for environmental prevention measures. Carbon dioxide emissions are considered to assess social costs, while five other gases—nitrogen oxides, particulate matter, sulfur dioxide, volatile organic compounds, and ammonia vapor—are included in investigating air pollution damage costs. Furthermore, the calculation of environmental prevention costs takes into account seven impact categories: global warming, photochemical oxidation, respiratory inorganic effects, human toxicity, ecotoxicity, eutrophication, and acidification.Results and DiscussionHere’s the edited text with corrections marked: The investigation reveals that the production of pomegranate juice emits approximately 0.12 kg CO2 eq of carbon, with a social cost of $0.0062 per functional unit. The primary contributors to carbon emissions are natural gas and electricity. Furthermore, the evaluation of air-polluting gases indicates a total cost of $0.021 for air pollution damage. Among the five considered gases, ammonia vapor, sulfur dioxide, and nitrogen oxides incur the highest damage costs. The assessment of environmental prevention costs demonstrates a total calculated cost of $0.026, with the impact categories of global warming and acidification making the most substantial contributions of 59% and 28%, respectively. This finding suggests that the majority of costs for preventing damage in pomegranate juice production should be focused on mitigating the effects of global warming. The consumption of natural gas and electricity during the pomegranate juice production process is the main source of carbon dioxide emissions and global warming. Additionally, in terms of acidification, the contributions of pomegranate, electricity, apple, natural gas, and sugar are noteworthy. Based on these findings, it is evident that the resources used in pomegranate juice processing, derived from fossil fuels, have the most significant impact on environmental damage. Therefore, one practical method to prevent the creation of these pollutants is the utilization of alternative bioproducts produced from biomass. Considering the substantial amount of pomegranate waste generated after juice processing,which is often not utilized; these wastes can be effectively employed to produce bioenergy, such as biogas. This approach not only prevents waste disposal but also offers economic and environmental benefits.ConclusionThis article provides an overview of the environmental impacts and associated costs of pomegranate juice production in Mashhad. Using the life cycle assessment approach, the study calculates the environmental impacts per functional unit (a 160g juice pack) and estimates the corresponding costs. The results indicate that the social cost of carbon emissions, the total damage costs of air pollution, and the total environmental prevention costs per functional unit are $0.0062, $0.021, and $0.026, respectively. These costs should be allocated to mitigating the environmental damage caused by pomegranate juice production in the region.AcknowledgmentsThe authors express their gratitude to Ferdowsi University of Mashhad for funding this research (Grant No. 54189).